Value–orientation of Entrepreneurs: A Critical Analysis - Manikahiya, C.Y.; Jhamtani, Anita; Padaria, R.N.; G, Letha Devi; Yadav, V.K. (Indian Journal of Extension Education, 2009)
Enterprises like floriculture, olericulture, apiary etc. have a potential for generating higher income opportunity for value addition and a huge market. It can be started with low investment. It is emerging as a potential area for agricultural entrepreneurs. The present study was designed keeping the agri-entrepreneurs in mind. Accordingly, the objective was formulated to study value-orientation of entrepreneurs. The research was purposively carried out in three districts of NCR Delhi viz. Sonepat, West Delhi and Gautam Buddha Nagar, because of intense micro-entrepreneurial activities in these areas . From three blocks (Rai, Alipur and Bisharkh) and three villages (Chauhanjoshi, Kisuk and Etera) were randomly selected. Thirty respondents comprising ten entrepreneurs from each village were selected randomly for this study. The collected data were tabulated, analyzed and interpreted with the help of appropriate statistical tools. The result of Q-sort indicated that honesty was highly important value for entrepreneurs. Self confidence, knowledge, innovativeness and self-dependence were perceived as very important values, whereas luck and religion were perceived as of very little importance for the entrepreneurs. Sixteen values which were relatively important i.e. values whose median scores were 5.5 and above were selected for the factor analysis. It revealed three factors greatly affecting the value-orientation of the entrepreneurs as, Entrepreneurial spirit value, family orientation value and perseverance.